Increased left ventricular muscle mass after long-term altitude training in athletes - Svedenhag, J.; Piehl-Aulin, K.; Skog, C.; Saltin, B. (Acta Physiologica Scandinavica, 1998)
The effects of long-term altitude training on altitude and sea-level physiological characteristics in elite endurance athletes were investigated. Seven Swedish elite cross-country skiers (five men, two women; mean age 27 years) spent 1 month training at 1900 m above sea level in Italy. Rollerski treadmill tests were performed before and 5 and 11 days after the altitude sojourn; three tests were also performed at altitude. Before and 1, 11 and 35 days after the altitude camp, echocardiographic and blood volume measurements were performed. The heart rates at both maximal (P < 0.05) and submaximal (P < 0.01) work loads were decreased by 5-9 beats min-1 at altitude. The haemoglobin concentration and haematocrit increased quickly at altitude with a corresponding decrease on return to sea level. The blood volume (7%) and total haemoglobin (3%) tended to be higher day 11 post-altitude (NS). There were no significant changes in diastolic internal diameter or wall thickness of the left ventricle, but the calculated cardiac left ventricular muscle mass was increased post-altitude (9-10%, P < 0.01). The maximal oxygen uptake increased in six of the seven skiers after the altitude training (day 11, mean 3%, NS). In conclusion, training at moderate altitude may cause a reduction in heart rates during exercise. Moreover, after long-term training at altitude, there may be an increase in the cardiac left ventricular muscle mass.